Features of Ensuring Regional Security in Central Asia: An Analysis of the Geopolitical Situation - Nurgul Akkozhina (Space and Culture, India)
With the continuation of the Russia-Ukraine war and the seizure of power in Afghanistan by the radical Taliban movement, the issue of ensuring countries’ security has taken a new dimension. These occurrences directly influence the global situation. This research aims to examine the primary security issues in Central Asia and identify regional threats within the evolving geopolitical context. To address the research objectives, various methods of cognition were employed, including historical, structural and functional, institutional, comparative, forecasting, political and legal analysis, classification, analogy, abstraction, analysis, and generalisation. The main results of this study include characterising the specifics of Central Asia and external threats to regional security, analysing the policies of the governments in the region to combat religious extremism and international terrorism, determining the prospects for establishing a collective defence organisation to develop mechanisms for countering these threats, and outlining the main activities of the Shanghai Cooperation Organisation and the Collective Security Treaty Organisation in maintaining regional stability and addressing the distribution of water and energy resources. The study also considered such security threats as cybercrime, human trafficking, separatism, interethnic conflicts, illegal migration, arms smuggling, and drug trafficking. This research's findings and materials have theoretical and practical applications. They may be helpful for researchers whose interests include the problems of national and regional security, political processes in post-Soviet Central Asia, and ethno-confessional conflicts in this area.